Interpersonal variability in timing strategy and temporal accuracy in rapid interception task with variable time-to-contact - Ijiri, T.; Shinya, M.; Nakazawa, K. (Journal of Sports Sciences, 2015)
In rapid interceptive actions such as hitting a baseball, cricket ball or tennis ball, ball speed varies between trials, and players have to compensate the time lag by controlling the moment of movement onset and movement duration. Previous studies have found that these two variables can flexibly co-vary and are robustly influenced by target speed (i.e. velocity-coupling effect: faster movement for faster target). However, some studies reported an interpersonal variability in the timing control strategy and the relationship between the strategy and temporal accuracy in rapid interception is unclear. We used a baseball-simulated rapid interceptive task to assess this issue. Under relatively easy time constraints, there was a large interpersonal variability, and participants were distinctively divided into two groups: those who mainly modulated their movement duration and those who mainly controlled their movement onset. When the time constraint became severe, the second strategy shifted to the first strategy in most of the second group participants. In the both cases, being able to mainly control movement onset resulted in higher temporal accuracy. These results suggest that minimising the velocity-coupling effect is an important factor to achieve high temporal accuracy in rapid interception.